A synthetic free fatty acid-regulated transgene switch in mammalian cells and mice. Issue 18 (14th September 2018) - Liu, Ying; Charpin-El Hamri, Ghislaine; Ye, Haifeng; Fussenegger, Martin
Abstract: Trigger-inducible transgene expression systems are utilized in biopharmaceutical manufacturing and also to enable controlled release of therapeutic agents in vivo . We considered that free fatty acids (FFAs), which are dietary components, signaling molecules and important biomarkers, would be attractive candidates as triggers for novel transgene switches with many potential applications, e.g. in future gene- and cell-based therapies. To develop such a switch, we rewired the signal pathway of human G-protein coupled receptor 40 to a chimeric promoter triggering gene expression through an increase of intracellular calcium concentration. This synthetic gene switch is responsive to physiologically relevant FFA concentrations in different mammalian cell types grown in culture or in a bioreactor, or implanted into mice. Animal recipients of microencapsulated sensor cells containing this switch exhibited significant transgene induction following consumption of dietary fat (such as Swiss cheese) or under hyperlipidaemic conditions, including obesity, diabetes and lipodystrophy.